Fluoride-dominated coating on Mg alloys fabricated by plasma electrolytic process in ambient non-aqueous electrolyte. (4th March 2021) - Qi, Yuming; Peng, Zhenjun; Wang, Lingqian; Zhou, Jiansong; Wang, Peng; Liang, Jun
ABSTRACT: In this work, the non-aqueous NH4 F-EG electrolyte was utilized for plasma electrolytic oxidation (PEO) process on AZ91 alloy to fabricate MgF2 -dominated coating at room temperature. Results revealed that the coating had a homogeneous composition and porous microstructure. Compared with the bare AZ91 samples, the coated samples showed a 109 mV nobler corrosion potential and two orders of magnitude lower corrosion current in neutral 3.5 wt% NaCl solution, while a 54 mV nobler corrosion potential and one orders of magnitude lower corrosion current in acidic 3.5 wt% NaCl solution (pH=3). Thus, it's unveiled a novel possibility to prepare non-oxide coating on Mg alloy by PEO process in non-aqueous electrolyte. And the MgF2 coating provided effective corrosion protection for Mg alloy both in neutral and acid corrosive media.